Pemberian Nafkah Anak Ditinjau Dari Undang-Undang No. 23 Tahun 2002 Tentang Perlindungan Anak - Ariansyah, Yudi; Harahap, Ikhwanuddin; Sirait, Adi Syahputra (Jurnal El-Thawalib, 2023)
This study examines how the responsibility for child maintenance after divorce and the factors behind the father not providing a living for the child after divorce in Silandit Village, South Padangsidimpuan District, Padangsidimpuan City. This type of research is field research with a qualitative approach. Primary data sources are research data sources obtained directly from the original source in the form of interviews with the Lurah and the community who are the object of research in Silandit Village, while secondary data can be in the form of books, Al-Qur'an, Journals, and other sources that related to research. Data collection techniques are by doing 3 methods in this study, namely by interview, observation, and documentation. The data analysis technique in this study is descriptive qualitative, namely describing, and summarizing various conditions, situations from various data collected, in the form of interviews and documents regarding the problems studied that occur in the field. The results of research on parental responsibility for children's livelihood after divorce in Silandit Village, there are three results, first: parents do not provide a living for their children after divorce and give it to their grandmother, Second: parents provide maintenance for their children but do not every month, Third: parents are irresponsible and neglect their obligations as a father. The factors behind parents not providing a living for their children are economic factors, psychological factors, parents remarrying factors, irresponsible factors, female parents being able to provide children's living expenses.